Camera lucida reflections on photography - Barthes, Roland (New York Hill and Wang, 1981)
This is a short book published in 1980 by the French literary theorist and philosopher Roland Barthes. It is simultaneously an inquiry into the nature and essence of photography and a eulogy to Barthes' late mother. The book investigates the effects of photography on the spectator (as distinct from the photographer, and also from the object photographed, which Barthes calls the "spectrum").

In a deeply personal discussion of the lasting emotional effect of certain photographs, Barthes considers photography as asymbolic, irreducible to the codes of language or culture, acting on the body as much as on the mind. The book develops the twin concepts of studium and punctum: studium denoting the cultural, linguistic, and political interpretation of a photograph, punctum denoting the wounding, personally touching detail which establishes a direct relationship with the object or person within it.

Camera Lucida, which takes its name from the optical device the camera lucida, consists of 48 chapters divided into two parts. The book is composed in free form and does not follow a particularly rigid structure. Barthes does not present a fixed thesis, but instead, highlights the evolution of his thought process as the book unfolds. As such, he consistently returns to ideas expressed in previous chapters to complete them, or even deny them. The story becomes increasingly personal in the second half, as scientific terminology, precise vocabulary, and numerous scholarly and cultural references give way to increasingly subjective and intimate language. The book is illustrated by 25 photographs, old and contemporary, chosen by the author. Among them are the works of famous photographers such as William Klein, Robert Mapplethorpe and Nadar, in addition to a photograph from Barthe's private collection.
Translation of: La chambre claire.
A gift of Ms. Jane Hofileña.
Keywords: Photography, Artistic; Photography -- Philosophy